2016
DOI: 10.1161/circimaging.115.004426
|View full text |Cite
|
Sign up to set email alerts
|

Association of Aortic Stiffness With Left Ventricular Remodeling and Reduced Left Ventricular Function Measured by Magnetic Resonance Imaging

Abstract: Background This study sought to assess cross-sectional associations of aortic stiffness assessed by magnetic resonance imaging (MRI) with left ventricular (LV) remodeling and myocardial deformation in the Multi-Ethnic Study of Atherosclerosis (MESA). Methods and Results Aortic arch pulse wave velocity (PWV) was measured with phase contrast cine MRI. LV circumferential strain (Ecc), torsion, and early diastolic strain rate (EDSR) were determined by tagged MRI. Multivariable linear regression models were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
80
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 32 publications
4
80
1
1
Order By: Relevance
“…17 Endothelial dysfunction is not irreversible, and many emerging nonpharmacological and pharmacological therapeutic strategies are under investigation that aim to reduce oxidative stress and promote nitric oxide release. 18 The observational study of Ohyama et al, 9 taken with other longitudinal data, provides supportive evidence of the role that declining arterial elasticity may have in the development of subclinical impairment of both systolic and diastolic functions.…”
Section: O'reganmentioning
confidence: 78%
See 3 more Smart Citations
“…17 Endothelial dysfunction is not irreversible, and many emerging nonpharmacological and pharmacological therapeutic strategies are under investigation that aim to reduce oxidative stress and promote nitric oxide release. 18 The observational study of Ohyama et al, 9 taken with other longitudinal data, provides supportive evidence of the role that declining arterial elasticity may have in the development of subclinical impairment of both systolic and diastolic functions.…”
Section: O'reganmentioning
confidence: 78%
“…17 Endothelial dysfunction is not irreversible, and many emerging nonpharmacological and pharmacological therapeutic strategies are under investigation that aim to reduce oxidative stress and promote nitric oxide release. 18 The observational study of Ohyama et al, 9 taken with other longitudinal data, provides supportive evidence of the role that declining arterial elasticity may have in the development of subclinical impairment of both systolic and diastolic functions.There are many approaches and technologies used to assess vascular stiffness that present both challenges and opportunities for advancing our understanding of hemodynamic factors in heart disease. 1 In the study of Ohyama et al,9 the velocity of the propagating systolic wavefront in the aorta was determined using phase contrast imaging-a noninvasive approach for assessing vascular stiffness that offers good agreement with intra-aortic pressure measurements.…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…In the Framingham study, exposure to elevated BP at baseline was associated with future development of LVH as assessed by echocardiography in both men and women [21]. Moreover, in line with a small study in 100 subjects free of overt cardiac disease [34], a cross-sectional magnetic resonance imaging study in 2093 MESA participants showed that higher proximal aortic stiffness was associated with LV concentric remodelling [35]. Furthermore, in 607 FLEMENGHO participants, in both men and women, we observed similar associations of longitudinal increases in LV wall thickness and relative wall thickness (a marker of concentric remodelling) with higher baseline PWV during a five-year follow-up period, independent of other important covariables (Fig.…”
Section: Sex-specific Cardiac Maladaptation To Hypertension and Artermentioning
confidence: 92%